Price Discrimination through a Distribution Channel: Theory and Evidence - Gerstner, Eitan; Hess, James D.; Holthausen, Duncan McC. (American Economic Review, 1994)
Price-discrimination practices are common, but they typically are analyzed in a framework in which firms sell directly to end users (Louis Phlips, 1981; Richard Schmalensee, 1981; Hal Varian, 1985; Gerstner and Holthausen, 1986). This direct-channel framework is valid for service industries such as entertainment and travel, where senior citizens buy reduced-price tickets to musical concerts, and children receive discounts on airfares and movietheater tickets. In the packaged-goods and durable-goods industries, however, manufacturers sell to retailers who sell to consumers. In indirect channels like these, price discrimination occurs when manufacturers target discounts1 to price-conscious consumers in the form of coupons and rebates. Consumers who do not use these discounts pay higher net prices. Because manufacturers cannot dictate consumer prices to retailers, analysis of price discrimination ought to take into account the pricing behavior of retailers (Michael Katz, 1987; Gerstner and Hess, 1991). While some researchers have studied coupons as a means for price discrimination (William Levedahl, 1984; Chakravarthi Narasimhan, 1984), they have done so in a direct-channel context and have ignored the role of retailers or other middlemen in the pricing and couponing process. In this paper we study price discrimination within a channel of distribution consisting of a single manufacturer and competitive retailers. In the model, the manufacturer pricediscriminates using a pull discount targeted at consumers with low reservation prices to reduce the net price these consumers pay for the product. Some consumers with higher reservation prices, who self-select not to use the discount, pay the full retail price for the product. The manufacturer chooses the wholesale price for the firm's product and the size of the price-discriminating pull discount, taking as given the markup percentage used by retailers. Joint determination of the manufacturer discount and retail markup is also considered. The paper's major finding is that a higher retail markup percentage influences the manufacturer to use price discrimination in a less intensive way (i.e., to reduce the size of the equilibrium pull discount as well as the wholesale price). The intuition behind this result is as follows. The greater the retail markup percentage, for a given wholesale price, the greater will be the retail price. The greater the retail price, the larger the pull discount will have to be to keep the low-reservation-price consumers in the market. But the manufacturer bears the entire cost of the discount, and a larger discount induces more nontargeted customers to use it. These two effects make price discrimination less profitable when markup percentage increases, so the manufacturer reduces its pull discount and in*Gerstner: Graduate School of Management, University of California, Davis, CA 95616, and Department of Economics, Haifa University, Haifa 31999, Israel; Hess: Department of Business Administration, University of Illinois, Champaign, IL 61820; Holthausen: Department of Economics, North Carolina State University, Box 7507, Raleigh, NC 27695. We thank Alastair Hall, Jeongwen Chiang, Randy Cooke, and Nick Ruotolo for their comments and assistance. 1Manufacturers who distribute products through retailers use push or techniques to increase sales. Under push, manufacturers offer inducements to retailers. When consumers shop for the product, the retailer has an incentive to promote the brand, thus pushing it through to consumers. Under pull, manufacturers offer incentives such as coupons or rebates directly to consumers. The manufacturers hope that demand will be pulled through the channel by consumers asking retailers for the promoted brand.